2020
DOI: 10.1056/nejmoa2020473
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Dexamethasone for Chronic Subdural Hematoma

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(180 citation statements)
references
References 27 publications
(36 reference statements)
5
159
1
2
Order By: Relevance
“…Clearly a rather robust inflammatory response of the brain to the initial SDH is elicited and persists ( 7 , 12 ). Recent trials have been directed at attenuating this response with dexamethasone or atorvastatin ( 19 , 20 , 37 ). There has also been much recent interest in middle meningeal artery (MMA) embolization for the treatment of cSDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly a rather robust inflammatory response of the brain to the initial SDH is elicited and persists ( 7 , 12 ). Recent trials have been directed at attenuating this response with dexamethasone or atorvastatin ( 19 , 20 , 37 ). There has also been much recent interest in middle meningeal artery (MMA) embolization for the treatment of cSDH.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for cSDH include surgery (15)(16)(17), observation and medications such as dexamethasone (12,(18)(19)(20) and endovascular obliteration of the meningeal artery (21)(22)(23)(24)(25). There have been numerous studies examining the different procedures.…”
Section: Figure 2 |mentioning
confidence: 99%
“…In fact, symptomatic CSDH patients showed less favorable outcomes compared to control group under the treatment of oral dexamethasone. 16 Repeating irrigation and drainage are still effective for recurrence of CSDH, however, with appropriate selection, this procedure is an important alternative particularly in the frail, anticoagulated or coagulopathy population. 15 There is ample evidence that contradicts a simple traumatic etiology for chronic subdural hematoma and alludes to a more active inflammatory and angiogenic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of comorbidities in the cSDH patient population was high (63%), and arterial hypertension, as well as cardiac arrhythmias, accounted for most of them (35% and 21%, respectively). On head CT imaging, cSDH had a median thickness of 21 [15][16][17][18][19][20][21][22][23][24][25] mm, were right-sided in 31%, leftsided in 41%, and bilateral in 28% of cases, while a midline shift was visible in 67% with a median of 6 [2-10] mm. Antithrombotics were present in more than half of all cSDH patients (51%) and were almost equally distributed between only anticoagulant (47%) and only antiplatelet (50%) drugs, with few patients (3%) receiving both.…”
Section: Patient and Treatment Demographicsmentioning
confidence: 99%
“…While not the focus of the current study, the association of peri-operative steroid use (which was not part of our treatment regimen for cSDH) with the necessity of repeat operations has been the focus of recent investigations and is currently under critical discussion: Several reports on beneficial effects of steroids on cSDH recurrence exist, but some authors also observed contradictory and even adverse effects [12,19,24,48]. Correspondingly, the very recently published multicenter, randomized DEX-CSDH trial has reported fewer repeat operations but at the same time also fewer favorable outcomes and more adverse events with a 2-week oral dexamethasone treatment compared to placebo at 6 months [21]. Although more prospective studies are currently underway, especially in more vulnerable patients with chronic comorbidities, the peri-operative administration of steroids should thus be evaluated with caution [29,30].…”
Section: Reoperationmentioning
confidence: 99%